Study on the forecast model of electricity substitution potential in Beijing-Tianjin-Hebei region considering the impact of electricity substitution policies. (September 2020) - Wang, Yongli; Wang, Shuo; Song, Fuhao; Yang, Jiale; Zhu, Jinrong; Zhang, Fuwei
Abstract: In recent years, China has introduced a series of energy substitution policies, aiming to achieve a fundamental change in the way of energy development. Firstly, based on the world energy model constructed by IEA, this paper determines the main driving factors in the field of power substitution, including economy, technology, policy, energy price and environmental factors. Secondly, based on the principle of system dynamics, a causal relationship diagram of five driving factors is constructed to clarify the feedback and linkage relationship between the factors. Finally, this paper proposes a hybrid prediction model combining Salp Swarm Algorithm (SSA) and Least Squares Support Vector Machines (LSSVM), namely SSA-LSSVM, which fully considers the influence of relevant factors of electric energy substitution, while avoiding the subjectivity of model parameter setting. The results show that the future development of electric energy substitution in the Beijing-Tianjin-Hebei region has maintained a rapid pace. The potential for electric energy substitution in the industrial production sector is large, and there is a large space for mining and operation optimization in the residential heating and transportation sectors. This paper provides a basis for the future development and improvement of the strategic plan of electric energy substitution in Beijing-Tianjin-Hebei region. Highlights: Electric energy substitution is one of the measures to optimize energy structure in Beijing-Tianjin-Hebei region. The influencing factors of electric energy substitution policy are analyzed in detail. The prediction method of electric energy substitution potential is proposed. Great potential of electric energy substitution in the fields of industry, residents and transportation.